Vertical rectus abdominis myocutaneous flap reconstruction of the perineal defect after abdominoperineal excision is associated with low morbidity. (18th September 2013) - Barker, T.; Branagan, G.; Wright, E.; Crick, A.; McGuiness, C.; Chave, H.
Abstract Aim To examine the short‐term outcomes of perineal reconstruction with a vertical rectus abdominis myocutaneous (VRAM) flap following abdominoperineal excision (APE). Method Retrospective case note review of all patients undergoing APE and primary VRAM reconstruction between July 2001 and February 2012 in a district general hospital tertiary referral centre for APE. Complications were categorized using the Clavien–Dindo classification, which grades complications from I to V in order of increasing severity. Results Fifty‐five consecutive patients (31 men, median age 65, range 38–84 years) underwent APE with VRAM flap reconstruction, 15 for anal cancer and 40 for rectal cancer. Median length of stay was 11 days but was significantly shorter in the laparoscopic group compared with the open group (8 vs 12 days; P < 0.01) and in patients who did not experience any complications (P < 0.05). Four patients (7%) had major complications (Grade 3 and above) directly related to the flap or donor site. Conclusion VRAM reconstruction of the perineum can be safely performed following APE with results that compare favourably with other techniques. Most flap complications are minor, although these are still associated with an increase in the length of hospital stay.